Corrosion and radiation resistant nanoceramic coatings for lead fast reactors. (1st August 2017) - Ferré, F. García; Mairov, A.; Iadicicco, D.; Vanazzi, M.; Bassini, S.; Utili, M.; Tarantino, M.; Bragaglia, M.; Lamastra, F.R.; Nanni, F.; Ceseracciu, L.; Serruys, Y.; et al.
Graphical abstract: Highlights: Al2O3 coatings grown on 1515Ti steel plates, cylinders and tubes. Coatings retain structural integrity upon thermal cycling, nanoimpact and scratch. Samples exposed to static Pb (550 °C, 1000 h, 4000 h, 10 −8  wt.% O). Selective leaching of Ni, Mn and Cr observed in uncoated samples. Corrosion avoided in coated samples, either pristine or irradiated. Abstract: Bare and Al2 O3 -coated austenitic steel samples are exposed to lead-fast-reactor relevant corrosive conditions. Selective leaching of Ni, Mn and Cr is observed in bare samples exposed to high temperature stagnant lead (550 °C, 10 −8  wt.% oxygen, 1000 and 4000 h). By contrast, corrosion is not observed in either pristine (4000 h) or irradiated (1000 h) coated samples. Further characterization and testing methods include SEM, TEM, STEM, EDS, cyclic nanoimpact, microindentation, scratch, and thermal cycling. Overall, the results show that the coatings retain structural integrity under the conditions investigated, which is a crucial prerogative for corrosion protection with ceramic coatings.